Конфліктологічна компетентність як показник рефлексивно-поведінкового компонента педагогічної толерантності майбутніх учителів - Гордієнко, Юлія; Gordienko, Yu. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті відображено результати теоретичного аналізу наукових підходів щодо визначення явища конфліктологічної компетентності як показника рефлексивно-поведінкового компонента педагогічної толерантності учителів іноземних мов початкової школи. Розкрито змістову сутність поняття «конфліктологічна компетентність». Виявлено, що у трактуваннях означуваного поняття простежується тяжіння до категорії «стратегії поведінки», та визначено функції конфліктологічної компетентності. Розглянуто види педагогічних конфліктів та причини їхнього виникнення, схарактеризовано особливості конфліктів у взаємодії між учителем та учнями. Привернуто увагу до негативних та позитивних функцій педагогічних конфліктів. Виділено комплекс умінь та навичок, які потрібно розвивати у процесі конфліктологічної професійної підготовки майбутніх учителів. Розглянуто стратегії виходу з конфлікту. Визначено, що толерантний учитель повинен бути обізнаним з різними стилями поведінки, але надавати перевагу співпраці як найбільш ефективному способу вирішення конфліктних ситуацій. The article reflects the results of the theoretical analysis of scientific approaches to the definition of the phenomenon of conflictological competence as an indicator of the reflective and behavioral component of pedagogical tolerance of future teachers of foreign languages in the elementary school. It has been revealed that interpretations of the studied concept tend to include the category of "behaviour strategies". Informational, regulatory, facilitative, reflective, preventive functions of the conflictological competence have been defined. The article describes the types of pedagogical interpersonal conflicts, reasons for their occurrence, the characteristic features of conflicts in the interaction between teacher and students. It has been determined that the occurrence of conflict situations in the educational process is contrary to the principles of tolerant interaction between teacher and pupils, it rather indicates professional incompetence of the teacher than blames the students for creating the atmosphere of conflict in learning. The attention has been drawn to the negative and positive functions of pedagogical conflicts. The article highlights the complex of skills that need to be developed in the process of professional conflictological training of future teachers. Such strategies of the conflict resolution as compromise, competition, avoidance, cooperation, conformity have been considered. It has been determined that a tolerant teacher should be familiar with various styles of behavior, but use mainly the strategy of cooperation as the most effective method of conflict resolution.
Conflictological competence as an indicator of the reflective and behavioral component of the pedagogical tolerance of future teachers
Keywords: педагогічна толерантність; pedagogical tolerance; конфліктологічна компетентність; педагогічний конфлікт; конфліктна ситуація; стратегія виходу з конфлікту; співпраця; conflictilogical competence; pedagogical conflict; conflict situation; strategy of conflict resolution; cooperation